Working with nature, working with Indigenous knowledge: Community priorities for climate adaptation in Samoa - Anita Latai-Niusulu; Susana Taua'a; Tuputau Lelaulu; Maibritt Pedersen Zari; Sibyl Bloomfield (Nature-Based Solutions)
The culturally diverse region of Moananui Oceania, is where many of the world's nations that are most impacted by climate change are located, including Samoa. Nature-based solutions (NbS) offer significant potential for effective climate change adaptation and are increasingly being explored and utilized in the region both in terms of (re)exploring traditional human designed living-systems created over connected land and oceanscapes, and in relation to contemporary NbS strategies. To explore nature-based adaptation agendas that link closely to Indigenous ecological knowledge and understandings of wellbeing, and that can enhance cultural connections to NbS in an urban climate change adaptation context, the Nature-based Urban design for Wellbeing and Adaptation in Oceania (NUWAO) Vaisigano Project in Samoa was conceived. The project examines and draws upon contemporary and traditional relationships between human settlements and nature in Samoa, as a means to advocate for regenerative urban environments that enhance entwined socio-ecological wellbeing and resilience as a climate change adaptation measure. We conducted a series of household interviews along a ridge-to-reef transect in the Vaisigano Catchment and then conducted fa'afaletui focus groups to ascertain community understandings and priorities related to NbS for climate change adaptation. Findings include that there is great potential in combining local Indigenous knowledges and worldviews with contemporary nature-based approaches to create culturally effective, just, and resilient climate change adaptation measures in Samoa, and in wider Moananui Oceania.